Dynamic Softening and Hardening Behavior and the Micro-Mechanism of a TC31 High Temperature Titanium Alloy Sheet within Hot Deformation - Kexin Dang (MDPI AG, 2021)
TC31 is a new type of α+β dual phase high temperature titanium alloy, which has a high specific strength and creep resistance at temperatures from 650 °C to 700 °C. It has become one of the competitive candidates for the skin and air inlet components of hypersonic aircraft. However, it is very difficult to obtain the best forming windows for TC31 and to form the corresponding complex thin-walled components. In this paper, high temperature tensile tests were carried out at temperatures ranging from 850 °C to 1000 °C and strain rates ranging from 0.001 s−1 to 0.1 s−1, and the microstructures before and after deformation were characterized by an optical microscope, scanning electron microscope, and electron back-scatter diffraction. The dynamic softening and hardening behaviors and the corresponding micro-mechanisms of a TC31 titanium alloy sheet within hot deformation were systematically studied. The effects of deformation temperature, strain rate, and strain on microstructure evolution were revealed. The results show that the dynamic softening and hardening of the material depended on the deformation temperature and strain rate, and changed dynamically with the strain. Obvious softening occurred during hot tensile deformation at a temperature of 850 °C and a strain rate of 0.001 s−1~0.1 s−1, which was mainly caused by void damage, deformation heat, and dynamic recrystallization. Quasi-steady flowing was observed when it was deformed at a temperature of 950 °C~1000 °C and a strain rate of 0.001 s−1~0.01 s−1 due to the relative balance between the dynamic softening and hardening. Dynamic hardening occurred slightly with a strain rate of 0.001 s−1. Mechanisms of dynamic recrystallization transformed from continuous dynamic recrystallization to discontinuous dynamic recrystallization with the increase in strain when it was deformed at a temperature of 950 °C and a strain rate of 0.01 s−1. The grain size also decreased gradually due to the dynamic recrystallization, which provided an optimal forming condition for manufacturing thin-walled components with the desired microstructure and an excellent performance.